2016
DOI: 10.1016/j.juro.2015.12.083
|View full text |Cite
|
Sign up to set email alerts
|

Focal Laser Ablation of Prostate Cancer: Phase I Clinical Trial

Abstract: Focal laser ablation of the prostate is feasible and safe in men with intermediate risk prostate cancer without serious adverse events or changes in urinary or sexual function at 6 months. Comprehensive biopsy followup indicates that larger treatment margins than previously thought necessary may be required for complete tumor ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
62
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 18 publications
7
62
0
1
Order By: Relevance
“…IPSS results demonstrated no significant changes in urinary symptoms for up to 18 months after ablation compared to baseline readings. This finding is consistent with other studies …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…IPSS results demonstrated no significant changes in urinary symptoms for up to 18 months after ablation compared to baseline readings. This finding is consistent with other studies …”
Section: Discussionsupporting
confidence: 94%
“…PSA measurements at 3–18 months following ablation demonstrated a significant decrease compared to baseline with a mean drop of 1.5 ng/mL at 18 months. Other studies also reported similar drop in PSA . This drop in PSA may be due to ablation of some benign prostatic tissue.…”
Section: Discussionsupporting
confidence: 56%
“…Using longitudinal coregistration, one could consistently re-visit the same gland location 57 , without limitations of implantable/imageable pellets proposed recently by Ghai et Tranchtenberg 58 . Recently, Natarajan et al 59 rose the question of assessment of treatment margin in their report of a phase 1 trial about focal therapy using in bore laser ablation with a transrectal approach. Our method may assist to discriminate infield/ outfield recurrence after focal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…After a series of experiments on phantoms, ex vivo tissues, and on in vivo animal models [99], MR thermometry has been employed during LA of HCC and liver tumors , prostate cancer, and metastases during the last decade [100,101,102]. Recent studies have shown the possibility of obtaining good spatial and temporal resolution and good precision [103].…”
Section: New Solutions To Guide Laser Ablationmentioning
confidence: 99%